2017
DOI: 10.1111/jpi.12449
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents endothelial cell pyroptosis via regulation of long noncoding RNA MEG3/miR‐223/NLRP3 axis

Abstract: Atherosclerosis (AS) is an inflammatory disease linked to endothelial dysfunction. Melatonin is reported to possess substantial anti-inflammatory properties, which has proven to be effective in AS. Emerging literature suggests that pyroptosis plays a critical role during AS progression. However, whether pyroptosis contributes to endothelial dysfunction and the underlying molecular mechanisms remained unexploited. This study was designed to investigate the antipyroptotic effects of melatonin in atherosclerotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
275
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(282 citation statements)
references
References 54 publications
7
275
0
Order By: Relevance
“…The MDA, GSH, and SOD were quantified by using commercial kits, according to the manufacturer's protocol (Zarfati, Avivi, Brenner, Katz, & Aharon, ). For MDA and SOD measurement (Y. Zhang, Zou, et al, ), the samples were rinsed with PBS and then homogenized and sonicated in lysis buffer on ice (B. Zhang, Hou, et al, ). After sonication, the lysed tissues were centrifuged at 10,000 g for 10 min to remove debris (Riehle & Bauersachs, ).…”
Section: Methodsmentioning
confidence: 99%
“…The MDA, GSH, and SOD were quantified by using commercial kits, according to the manufacturer's protocol (Zarfati, Avivi, Brenner, Katz, & Aharon, ). For MDA and SOD measurement (Y. Zhang, Zou, et al, ), the samples were rinsed with PBS and then homogenized and sonicated in lysis buffer on ice (B. Zhang, Hou, et al, ). After sonication, the lysed tissues were centrifuged at 10,000 g for 10 min to remove debris (Riehle & Bauersachs, ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely documented that MEG3 affects the physiological and pathological progression of a variety of human diseases, including cancers, hypoxia-induced pulmonary hypertension, diabetic retinopathy, pulmonary fibrosis, diabetes, nonalcoholic fatty liver disease, ischemic neuronal death, and Hirschsprung's disease as well as atherosclerosis and vascular disease (Wapinski and Chang, 2011;Adams et al, 2017;He et al, 2017). Zhang et al (2018) demonstrated that lncRNA MEG3 enhanced pyroptosis in HAECs and exerted its function via modulation of MEG3/miR-223/ NLRP3 axis in atherosclerosis. However, the role of MEG3 and its underlying molecular mechanisms in macrophages treated with ox-LDL are largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, chemically N‐acetyl‐5‐methoxytryptamine, has been proved to exert its protective properties in a variety of cardiovascular diseases . Recent studies have reported that melatonin has the ability to protect against diabetes‐induced cardiac dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, chemically N-acetyl-5-methoxytryptamine, has been proved to exert its protective properties in a variety of cardiovascular diseases. [11][12][13][14][15] Recent studies have reported that melatonin has the ability to protect against diabetesinduced cardiac dysfunction. 16,17 Our previous study demonstrated that melatonin alleviated posttraumatic myocardial injury and cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%